Análise e comparação de desgaste em materiais para facas de moinho para polímeros - Lombarde, Gustavo (2022)
Knowing the difficulties of recycling plastics, the main one being the excessive maintenance required in the mills, due to the existence of the plastics grinding process together with dirty water, generating severe wear on the cutting edges of the knives composed of Iron-Carbon, steel 5160 more specifically. The objective of this work is to find a possible solution or improvement for the time between maintenance of the equipment, carrying out tests with a sphereondisc reciprocal tribometer with an oxidationresistant material, stainless steel 440C, as a proposal for a possible substitute material for the material currently used as material for cutting knives in mills. The stainless steel showed lower values of friction coefficient than the alloy used, however, with some reservations in relation to the quality of the specimens and the method used in the tests.